ADDIE-Based Offline Digital Modules for Pre-Service Islamic Teacher Education: Advancing Digital Literacy and Pedagogical Competence - Alfurqan Alfurqan; Budi Santoso Wibowo; Ummiatul Fitri; Wuri Syaputri; Annisaul Khairat; Moh In’ami; Zilham Usral (Online Learning In Educational Research (OLER), 2026)
The integration of digital technology into teacher education has become increasingly important for supporting curriculum reforms and preparing future educators for technology-enhanced instruction. Despite this trend, limited attention has been given to offline digital learning resources designed for pre-service Islamic education teachers in contexts where internet access remains constrained. This study investigated the effectiveness of ADDIE-based offline digital learning modules in supporting the implementation of Kurikulum Merdeka while strengthening digital literacy and pedagogical competence. A concurrent mixed-methods approach was employed involving 50 pre-service Islamic education teachers at Universitas Negeri Padang during a six-week implementation period. Quantitative data were collected through pre- and post-intervention assessments, while qualitative evidence was gathered from interviews and participant reflections to provide deeper insights into the learning experience. The findings indicate that the offline digital modules substantially improved participants’ digital literacy and pedagogical competence, enabling them to design curriculum-aligned lessons and adopt more student-centered instructional practices. Participants also reported increased confidence in integrating digital technologies into teaching, although challenges related to offline functionality and varying levels of digital readiness remained. This study extends the literature by demonstrating that context-responsive offline digital modules can serve as an effective instructional solution for teacher education in low-connectivity environments. The findings offer practical implications for designing inclusive digital learning resources that support equitable technology integration and sustainable curriculum implementation in teacher education